Sustaining power resources through energy optimization and engineering - Vasant, Pandian; Voropaĭ, N. I. (Nikolaĭ Ivanovich) (Advances in computer and electrical engineering (ACEE) book series, 2016)
"This book highlights the sustainable development and efficient operation of energy systems being provided to consumers by featuring emergent research and trends within the area of power optimization and engineering"--Provided by publisheR